Effects of Humanin on Spermatogenesis and Mitochondrial Membrane Potential in Male Rats - Canpolat, Sinan; Gokdere, Ebru; Ercan, Eda Coban; Gungor, Ibrahim Halil; Kom, Rumeysa Esra; Akipek, Mehmet Emre; Turk, Gaffari (Wiley, 2025)
[Abstract Not Available]
Keywords: Humanin; Sperm Parameters; Mitochondrial Membrane Potential